MHD flow and heat transfer of a hybrid nanofluid past a nonlinear surface stretching/shrinking with effects of thermal radiation and suction - Jamaludin, Anuar; Jaafar, A'isyah; Waini, Iskandar; Nazar, Roslinda; Pop, Ioan Mihai (Elsevier B.V., 2022)
The essence of this study is to explore the nonlinearly stretching/shrinking hybrid nanofluid in terms of its steady flow and heat transfer with the effects of magnetohydrodynamics (MHD), thermal radiation, and suction. The governing partial differential equations are modified by similarity solution into nonlinear ordinary differential equations and solved numerically by bvp4c. The effects of profile on both velocity and temperature, the skin friction coefficient, and the Nusselt number were examined. It was discovered that dual solutions were present, and water has superior heat transfer performance compared to nanofluids and hybrid nanofluids. The thermal boundary layer thickness increases as magnetic and suction parameters increase. According to the stability analysis, first solution is steady, and second solution is unsteady.